THE PRODUCT OF THREE k-GENERALIZED LUCAS NUMBERS AS REPDIGITS - Altassan, Alaa; Alan, Murat (PUSHPA PUBLISHING HOUSE, 2025)
In this paper, we search all repdigits which are products of arbitrary three terms of k-generalized Lucas sequences. Thus, we find all nonnegative integer solutions of the Diophantine equation (LnLmLl(k) )-L-(k)-L-(k)= a(10(d)-1/9) where n >= m >= l >= 0 and 1 = 2 and d >= 1.
Keywords: k-generalized Lucas sequences; k-Lucas numbers; linear forms in logarithms; Lucas numbers; FIBONACCI NUMBERS; Mathematics